Trade liberalization and the returns to education: A pseudo-panel approach - Andy Dickerson; Francis Green; Jorge Saba Arbache (University of Kent, Department of Economics, 2001)
We investigate the impact of trade liberalization on wages and the returns to education in Brazil. Our pseudo-panel estimates of the returns are significantly lower than OLS estimates, signifying omitted ability bias in traditional cross-section estimated returns in developing countries. Trade liberalization impacted on wages and the returns to education in both traded and non-traded sectors, suggesting important spill-over effects. Wages in both sectors fell in the period immediately after trade reform, with some compression of the skilled wage premium especially at the top of the distribution. Subsequently, there has been some recovery in wages, especially in the non-traded sector.
Keywords: J31; C23; 330; Trade Liberalisation; Returns to Education; Pseudo-Panel; Außenhandelsliberalisierung; Lohn; Bildungsertrag; Brasilien